Identifikasi Modal Sosial pada Sistem Pembiayaan Tanpa Agunan (Studi pada Koperasi Pandawa Kecamatan Sukun Kota Malang) - Supar di; Asfi Manzilati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The purpose of this study was to determine how the shape and role of social capital in the form of a trust, norm and social networks in finance without collateral in Koperasi Pandawa. By using qualitative method with a case study approach, it could be concluded that: (1) the trust is able to create a personal guarantee that allows customers to access financing in cooperation with the Pandawa materially limited warranty; (2) norm which translates into value together as